African evangelicalism and the transformation of Africa - Olúpǫ̀nà, Jacob Kę́hiǹdé (Race, religion, and politics series, 2025)
"What is the impact of Evangelical Christianity on Africa? Evangelical Christianity and the Transformation of Africa will answer this question. Evangelical Christianity is manifesting into a strong presence in African states, perhaps more than in any other place in the world. Given its exponential rise in Africa, it is increasingly clear that Christianity in its evangelical form is exercising significant influence in virtually all spheres of life, defining the essence of public and private life. Drawing on original works from leading scholars in humanities and social science disciplines-such as Afe Adogame, Yolanda Covington-Ward, Jacob Olupona, Derek Peterson, Shobana Shankar, and Nimi Wariboko, this volume endeavors to produce a comprehensive study of Evangelical Christianity in Africa, paying careful attention to disciplinary interconnections, as well as social, cultural, political, and economic forces. Among other subjects, essays in this volume address examples of evangelical subjectivity and identity formation against the current political backdrops of Nigeria, Kenya, the Democratic Republic of Congo, and other nations. While the book works to convey the core elements of the evangelical movement across the African continent, it recognizes the importance of its diverse manifestations, giving additional focus to Pentecostal groups and their distinct social, cultural, and political engagements. At the same time, it works to correct the unwarranted saturation of attention given to Pentecostal/Charismatic movements in recent scholarship and expands the study of evangelicalism in Africa into the sphere of mainline churches and extra-ecclesial organizations. Authors also reflect on the ways that the African diaspora and transnational ties contribute to the make up of contemporary African evangelicalism. In short, this edited volume examines how the centrality of religion in African affairs-political, economic, cultural, ideological domains-has contributed to turning Evangelical Christianity into the official face of the Christian Church in Africa today"